Diet of the exotic Rainbow Trout in the critical habitat of the threatened Hooded Grebe - Lancelotti, Julio Lucio (2015)
The lakes of the basaltic plateaus of Patagonia represent the only reproductive habitat for the critically endangered Hooded Grebe (Podiceps gallardoi). More than 50 of these naturally fishless lakes have been stocked with the exotic Rainbow Trout (Oncorhynchus mykiss). While the available information suggests that the diet composition of trout and Hooded Grebes could overlap, to date no formal studies of the diet of Rainbow Trout in these aquatic environments have been published. We characterized the diet of trout in one of the primary reproductive areas of the Hooded Grebe based on the analysis of the gut contents of 177 individuals, from 9 lakes. Amphipods were clearly the most dominant group of prey, quantified as frequency of occurrence and proportion by weight. The condition factor of trout and the abundance of amphipods in the stomach contents showed a functional relationship, suggesting that the wellness of trout depends on the availability of this prey. Amphipods also represent a primary prey for the Hooded Grebe, suggesting a strong dietary overlap with the trout. The presence of trout may generate processes of competition that could affect the survival of the Hooded Grebe. This interaction may be particularly relevant in large vegetated lakes, where the Hooded Grebe reproduces.